Elastohydrodynamic lubrication for bio-based lubricants in rectangular conjunction - Ibrahim, Alia (2010)
Knowledge of tribology is very important for successful design of machine elements. The most effective mean of overcome failures in machine elements is by proper lubrication. With the presence bio-based lubrications in the industry, the tribology understanding will changed significantly and will directly affect the performance and reliability to the machine elements. In this study, involute spur gear is used and remodeled using computational fluid dynamic software to simulate speed and squeeze phenomena behaviours. The gear teeth load is treated in a simplified idealistic way according to the experimental gear load spectrum. This analysis will enable the study of elastohydrodynamic lubrication in rectangular conjunction with different type of bio-based lubricants. Emphasis of analysis is focused on the speed and dynamic pressure distribution along the pinion surface. For each type of lubricant, computations were carried out in sixteen different low speeds which are 1.00 m/s until 0.05 m/s and 0.01 m/s. The results show that computer modelling exercise have demonstrated CFD with standard k-epsilon model is suitable for modelling a rectangular conjunction.